Does family matter? Venture capital cross-fund cash flows - Roman Kräussl; Kalle Rinne; Huizhu Sunc (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
Venture capital (VC) funds backed by large multi-fund families tend to perform substantially better due to cross-fund cash flows (CFCFs), a liquidity support mechanism provided by matching distributions and capital calls within a VC fund family. The dynamics of this mechanism coincide with the sensitivity of different stage projects owing to market liquidity conditions. We find that the early-stage funds demand relatively more intra-family CFCFs than later-stage funds during liquidity stress periods. We show that the liquidity improvement based on the timing of CFCF allocation reflects how fund families arrange internal liquidity provision and explains a large part of their outperformance.
urn:nbn:de:hebis:30:3-689720
Keywords: G24; G23; G34; 330; Venture capital; Fund family; Subsidization; Liquidity; Performance